Snake Ladder Modification Boardgame - Muhammad Aldiansyah Najib Amrullah; Aloung Candrika; Naufali Dimas Mahendra; Fauzi Kurniawan Asshidiqie; Muhammad Setiyawan (Jurnal Indonesia Sosial Sains, 2025)
This research explores the modification of the traditional Snake and Ladder board game into an educational tool aimed at enhancing memory and basic calculation skills among elementary school children aged 10–11 years. The study addresses the need for engaging learning methods by integrating mathematical challenges, such as addition, subtraction, multiplication, and division, into the game mechanics. The background highlights the game’s potential to combine entertainment with education, fostering cognitive development and social interaction. The objective of this research is to design and test a modified Snake and Ladder board game that serves as an effective educational medium. The methodology involved observational activities, interviews with school principals, and literature reviews of elementary school materials. The game components include question cards, penalty cards, dice, and pawns, with rules designed to reinforce learning through interactive play. Testing was conducted with 10 elementary school students, and feedback was collected via questionnaires. Findings indicate that the game successfully improved students' engagement and understanding of basic math concepts. The visual design and interactive elements were well-received, making learning more enjoyable. The research concludes that the modified board game is a viable tool for educational purposes, offering implications for future applications in classroom settings to enhance traditional teaching methods.